Peer Response in Second Language Writing Classrooms - Liu, Jun, 1959- (Book collections on Project MUSE., 2002)
"Like much of the process writing approach, peer response activities have become commonplace in second language writing classrooms - despite the fact that research has not conclusively documented their usefulness. Liu and Hansen provide a balanced analysis of the pros and cons of peer response but argue that most unsuccessful attempts are due to a lack of proper training of "peers." They advocate for thoughtful, well-planned preparation of students for collaborative work and a sensitive, supportive teacher throughout the process."--Jacket